NeuroPort: Retractor tubular personalizado para cirugías mínimamente invasivas fabricado mediante impresión 3D por estereolitografía - Gonzalez Leal, Cindy Jannet; Torres Cisneros, Carlos; Cervantes Castro, M. E.; Morales Gómez, J. A.; García Estrada, E.; De La Rosa Hernandez, Gerardo Adrian; Cervantes García, O. E. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
NeuroPort is a low cost customized biodevice for minimal invasion surgeries designed within Servicio Neurocirugía UANL and Departamento de Ingeniería Biomédica; and manufactured by stereolithography, a high- resolution 3D printing method. This biodevice provides a channel of approach for subcortical and intraventricular cerebral surgical procedures with an intended use in the treatment of diseases such as brain tumors, anomalies or vascular malformations, parenchymal hematomas, among others. It has a design that minimizes tissue damage by displacing the tissues of the brain during the advance toward the desired abnormality; in addition to its integration with neuronavigational equipment and its own lighting system. All these features designed to make the surgical procedure faster and safer for the patient, facilitating the work of the neurosurgeon.